The Influence of Convective Aggregation on the Stable Isotopic Composition of Water Vapor - Joseph Galewsky; Matthias Schneider; Christopher Diekmann; Addisu Semie; Sandrine Bony; Camille Risi; Kerry Emanuel; Helene Brogniez (AGU Advances, 2023)
Abstract Remote sensing datasets of water vapor isotopic composition are used along with objective measures of convective aggregation to better understand the impact of convective aggregation on the atmospheric hydrologic cycle in the global tropics (30°N to 30°S) for the period 2015–2020. When convection is unaggregated, vertical velocity profiles are top‐heavy, mixing ratios increase and water vapor δD decreases as the mean precipitation rate increases, consistent with partial hydrometeor evaporation below anvils into a relatively humid atmospheric column. Aggregated convection is associated with bottom‐heavy vertical velocity profiles and a positive correlation between mixing ratio and δD, a result that is consistent with isotopic enrichment from detrainment of shallow convection near the observation level. Intermediate degrees of aggregation do not display significant variation in δD with mixing ratio or precipitation rate. Convective aggregation provides a useful paradigm for understanding the relationships between mixing ratio and isotopic composition across a range of convective settings. The results presented here may have utility for a variety of applications including the interpretation of paleoclimate archives and the evaluation of numerical simulations of convection.